Effect of child health status on parents’ allowing children to participate in pediatric research - Vanhelst Jérémy; Hardy Ludovic; Bert Dina; Duhem Stéphane; Coopman Stéphanie; Libersa Christian; Deplanque Dominique; Gottrand Frédéric; Béghin Laurent (BMC Medical Ethics, 2013)
Abstract Background To identify motivational factors linked to child health status that affected the likelihood of parents’ allowing their child to participate in pediatric research. Methods Parents were invited to return their completed questionnaires anonymously to assess motivational factors and factors that might improve participation in pediatric research. Results Of 573 eligible parents, 261 returned the completed questionnaires. Of these, 126 were parents of healthy children (group 1), whereas 135 were parents of sick children who were divided into two groups according to the severity of their pathology, i.e., 99 ambulatory children (group 2) and 36 nonambulatory children (group 3). The main factor motivating participation in a pediatric clinical research study was “direct benefits for their child” (87.7%, 100%, and 100% for groups 1, 2, and 3, respectively). The other factors differed significantly between the three groups, depending on the child’s health status (all p < 0.05). Factors that might have a positive impact on parental consent to the participation of their child in a pediatric clinical research study differed significantly (χ2 test, all p ≤ 0.04), depending on the child’s health status. The main factor was “a better understanding of the study and its regulation” for the healthy children and ambulatory sick children groups (31.2% and 82.1%, respectively), whereas this was the third factor for the nonambulatory sick children group (50%). Conclusions Innovative strategies should be developed based on a child’s health status to improve information provision when seeking a child’s participation in pediatric research. Parents would like to spend more time in discussions with investigators.